Contabilidad gubernamental, postulados básicos de contabilidad (PBCG) y su fiscalización - Piñón Escamilla, Inés del Rosario (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
According to the constitutional changes, it is important to lay the fundamental groundwork normaran the Government accounting, basic principles of accounting (PCCG) and its control, "mandatory" according to the General Law on governmental accounting for the executive powers, legislative and judiciary of the Federation, federal entities and the Government body in our country that is Mexico. That it will influence significantly in the Latin American context and overall, in terms of accounting and control. The CONAC is control and coordinating body established for the accounting harmonization which is carried out gradually and standard legal bases and accounting of public accounts, of all the governmental system of Mexico. The present thesis work’s the method of research is qualitative and descriptive research, which includes historical, background, development studies of the same General Law on governmental accounting and its current monitoring for obtaining conclusions and recommendations. Providing knowledge for the development and empowerment in the short, medium and long term established in the same referent law.

De acuerdo a los cambios constitucionales, es muy importante sentar las bases fundamentales que normaran la Contabilidad Gubernamental, Postulados Básicos de Contabilidad (PCCG) y su Fiscalización, con “carácter obligatorio” de acuerdo a la Ley General de Contabilidad Gubernamental para los poderes Ejecutivo, Legislativo y Judicial de la Federación, entidades federativas y de todo el órgano gubernamental de nuestro país que es México. Que influirá de manera significativa en el contexto Latinoamericano y global, en cuanto a la Contabilidad y su Fiscalización. El CONAC, es órgano de control y coordinación establecida para la Armonización Contable que se efectúa gradualmente y norma las bases jurídicas y contables de las cuentas públicas, de todo el sistema gubernamental de México. El método de investigación del trabajo de tesis, es cualitativo y de investigación descriptiva, donde se incluyen estudios históricos, antecedentes, del desarrollo de la misma Ley General de Contabilidad Gubernamental y su actual seguimiento para la obtención de conclusiones y recomendaciones. Aportando conocimientos para su desarrollo y potenciación a corto, mediano y largo plazo establecido en la misma ley referente.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2011-0187; PBCG; Fisco; NIF; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5976